Harnessing the Power of Invariant Natural Killer T Cells in Cancer Immunotherapy - Bedard, Melissa; Salio, Mariolina; Cerundolo, Vincenzo (Frontiers in Immunology, 2017)
Invariant Natural Killer T (iNKT) cells are a distinct subset of innate-like lymphocytes bearing an invariant T-cell receptor, through which they recognize lipid antigens presented by monomorphic CD1d molecules. Upon activation, iNKT cells are capable not only of having a direct effector function, but also of trans-activating NK cells, maturing dendritic cells and activating B cells, through secretion of several cytokines and cognate TCR-CD1d interaction. Endowed with the ability to orchestrate an all-encompassing immune response, iNKT cells are critical in shaping immune responses against pathogens and cancer cells. In this review, we examine the critical role of iNKT cells in anti-tumour responses from two perspectives: i) how iNKT cells potentiate anti-tumour immunity and ii) how CD1d positive tumour cells may modulate their own expression of CD1d molecules. We further explore hypotheses to explain iNKT cell activation in the context of cancer and how the anti-tumour effects of iNKT cells can be exploited in different forms of cancer immunotherapy, including their role in the development of cancer vaccines.